Law Enforcement Against Narcotics Trafficking Crimes in Tapaktuan: (Research Study at the South Aceh Police) - Firliansyah, Jericho; Yahya, Faisal; Saifullah, Saifullah (Teunuleh Publisher, 2025)
This study discusses law enforcement against narcotics trafficking crimes in the jurisdiction of the South Aceh Police, namely Tapaktuan. Although various preemptive, preventive, and repressive efforts have been carried out in accordance with the provisions of Law Number 35 of 2009. The analysis uses Soerjono Soekanto's law enforcement theory which emphasizes three main elements, namely, legal structure, legal substance, and legal culture. Where the legal structure is one of the most important factors. Because the quality of law enforcement, one of which is the police, greatly affects the success or not of law enforcement. In its implementation, law enforcement carried out by the South Aceh Police has not been optimal. Which shows that the main obstacles lie in the limitation of personnel, inadequate infrastructure, low public legal awareness, and the complexity of the increasingly organized narcotics trafficking network. The method used is empirical legal research with a qualitative approach through direct interviews with the South Aceh Police Narcotics Headquarters and secondary data collection. These findings underscore the need for a comprehensive strategy involving strengthening apparatus resources, improving operational facilities, and intensive collaboration between the police, local governments, and the community to reduce the rate of narcotics trafficking in South Aceh